2008
DOI: 10.1098/rsta.2008.0125
|View full text |Cite
|
Sign up to set email alerts
|

Early differentiation of the Earth and the Moon

Abstract: We examine the implications of new 182 W and 142 Nd data for Mars and the Moon for the early evolution of the Earth. The similarity of 182 W in the terrestrial and lunar mantles and their apparently differing Hf/W ratios indicate that the Moon-forming giant impact most probably took place more than 60 Ma after the formation of calcium-aluminium-rich inclusions (4.568 Gyr). This is not inconsistent with the apparent U-Pb age of the Earth. The new 142 Nd data for Martian meteorites show that Mars probably has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 64 publications
4
19
0
Order By: Relevance
“…Therefore, if the hidden reservoir is very old, it must be produced by (and therefore postdate) crystallization of the terrestrial magma ocean. This observation is seemingly difficult to reconcile with the non-chondritic 142 Nd composition of the Bulk Silicate Moon (See Section 2), as this would require isolation of the hidden reservoir before the giant impact Bourdon et al, 2008). In the following section, we investigate mass balance relationships in the mantle-crust system using the nonchondritic BSE parameters defined in Section 2.…”
Section: A 4-reservoir Model Using Chur Parametersmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, if the hidden reservoir is very old, it must be produced by (and therefore postdate) crystallization of the terrestrial magma ocean. This observation is seemingly difficult to reconcile with the non-chondritic 142 Nd composition of the Bulk Silicate Moon (See Section 2), as this would require isolation of the hidden reservoir before the giant impact Bourdon et al, 2008). In the following section, we investigate mass balance relationships in the mantle-crust system using the nonchondritic BSE parameters defined in Section 2.…”
Section: A 4-reservoir Model Using Chur Parametersmentioning
confidence: 91%
“…Because the presentday 143 Nd signature of the MORB source puts limits on the magnitude of this early Sm/Nd fractionation, the hidden reservoir would have had to form less than 30 Myr after formation of the solar system (Boyet and Carlson, 2005), and probably less than 10 Myr if the effect of continental crust extraction on the 143 Nd signature of the depleted mantle is taken into account Korenaga, 2009). A major difficulty arises from the fact that this event needs to have taken place prior to the giant impact (Touboul et al, 2007;Bourdon et al, 2008;Halliday, 2008), a constraint confirmed by recent assessments of lunar composition Touboul et al, 2009). However, it is difficult to envision how a differentiated reservoir could have survived mixing in an entirely molten mantle (Canup, 2004), and in which the characteristic timescale of homogenization is expected to be no longer than a week (Pahlevan and Stevenson, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…First, the most recent W isotope data for the Moon now shows it to have identical e 182 W for the Earth (Touboul et al, 2007(Touboul et al, , 2009. This would give a mean accretion age for the Moon at no earlier than 4.517 Ga (52 Ma ONC ) to no later than 4.417 Ga (152 Ma ONC , Touboul et al, 2007Touboul et al, , 2009Bourdon et al, 2008;Halliday, 2008). Solidification of a global-scale magma ocean as early as 4.44 Ga ($129 Ma ONC ) as constrained by KREEP source formation at this time , would reduce the crystallization time to a maximum of $60-80 Ma after accretion of the Moon and possibly much less (Taylor et al, 2009).…”
Section: Implications For Early Moon Evolutionmentioning
confidence: 93%
“…This difference may have resulted from 2 processes. One possibility is nebular materials that accreted to make the bulk Earth may have had a slightly higher Sm/Nd ratio than those materials that accreted to make average chondrites Bourdon et al, 2008). An alternative possibility is that the bulk Earth has an identical 142 Nd/ 144 Nd ratio to that of the average solar system but there is an early-formed missing or hidden reservoir with a subchondritic Sm/Nd ratio that offsets the $20 ppm higher 142 Nd/ 144 Nd ratio observed in all measured terrestrial materials that are accessible relative to the average solar system.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation